2013
DOI: 10.1093/ije/dyt151
|View full text |Cite
|
Sign up to set email alerts
|

The joint association of anxiety, depression and obesity with incident asthma in adults: the HUNT Study

Abstract: This study suggests that having anxiety or depression symptoms contributes to the development of asthma in adults. The risk of asthma may be further increased by the interaction between anxiety or depression symptoms and obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 42 publications
1
35
0
1
Order By: Relevance
“…As in our trial, other studies have shown that depression is more common in women [24] and in populations with higher unemployment [25] and lower socio-economic status [26]. Anxiety is the most common comorbidity [27] and it is also correlated witho obesity [28]. …”
Section: Resultssupporting
confidence: 64%
“…As in our trial, other studies have shown that depression is more common in women [24] and in populations with higher unemployment [25] and lower socio-economic status [26]. Anxiety is the most common comorbidity [27] and it is also correlated witho obesity [28]. …”
Section: Resultssupporting
confidence: 64%
“…Other studies have also shown that diagnosed asthma and current wheezing were associated with diagnosed depression and anxiety [31,32]. An increased risk of incident asthma at follow-up was found in adults who reported symptoms of anxiety or depression at baseline in a large prospective study on the general population of Norway [33].…”
Section: Discussionmentioning
confidence: 90%
“…Patients who are actively involved in a trusting nurse-patient relationship have been found to experience increased adherence to treatment protocols (Elder et al, 2012;Blackstock, Addison, Brennam, & Alao, 2012), increased likelihood of lifestyle and behavioral change (Jones, Carson, Bleich, & Cooper, 2012), and higher patient satisfaction with care (Shan et al, 2016;Bohnert, Zivin, Welsh, & Kilbourne, 2011), leading to improved healthcare outcomes. In addition, Brumpton et al, (2013) ascertained the therapeutic effect of a trusting nurse-patient relationship. They found that chronic stress acted as a pathologic trigger in asthma incidents among adult patients, and by controlling stress through the trusting nurse-patient relationship, asthma incidents were reduced.…”
Section: Trusting Nurse-patient Relationshipmentioning
confidence: 99%